KONSERVATISME AKUNTANSI DAN DETERMINASINYA - Marlia Dina Karantika; Ardiani Ika Sulistyawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
The purpose of financial statements, among others, provide reliable financial information regarding keunagan position and results of operations of the company at a certain period, as well as provide financial information that can help the parties concerned to interpret the conditions and the potential of a business. In presenting the financial statements of each company in selecting accounting methods can be used to produce different financial statements - depending on each company in accordance with the wishes and needs of the company or in other words, companies are free to choose the accounting method used in accordance with the conditions and the measures taken by the company. In the accounting process in order to produce quality information and useful, the company faced with the constraints (constraints) one of them is conservatism. The study was conducted involving 120 manufacturing companies taahun books from 2010 to 2014 by using purposive sampling method. The research proves that conenant debt and firm size effect on accounting conservatism but not so with other fariabel are growth opportunities, managerial ownership, institutional ownership and public ownership. Suggestions for further research should add or replace other variables that have not been included in this study that have an influence on conservatism.